Animal models in influenza research - Zhou, J.; Hemmink, Johanneke D.; Whittaker, C.J.; Shelton, H.A.; Peacock, T. (Humana Press, 2025)
Animal model systems for human and animal influenza virus infection and transmission have been established to address research questions which cannot be addressed using in vitro models. Several animal models are widely used, including mice, guinea pigs, hamsters, ferrets, pigs, poultry, nonhuman primates, and others. Each animal model has its own strength and weaknesses, which should be taken into consideration to select the appropriate animal model to use. This chapter will describe standard protocols relevant for in vivo experiment, including procedures required prior to the start of the animal experiment and sample processing. The animal models described in this chapter are mice, hamsters, guinea pigs, ferrets, pigs, and chickens.